Strategi Terpadu Peningkatan Produksi Padi di Indonesia : Suatu Analisis Literatur Komprehensif - Tri Wahyuni Damayanti; Sazuli Sazuli; Susila Isma; Shovia Alkesya Mardila; Reflis Reflis (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
Increasing rice production is a national strategic priority given its role in maintaining food security and economic stability in the community. This study aims to analyze strategies for increasing rice production in Indonesia through a literature review approach based on relevant scientific articles. The analysis was conducted to identify the main factors that affect rice productivity and to formulate comprehensive strategies covering aspects of cultivation technology, land and water management, institutions and extension, production risk mitigation, and socioeconomic factors. The results of the study show that modern cultivation technology, especially the use of new superior varieties, the legowo planting system, and balanced fertilization, are the main foundations for increasing productivity. However, the success of technology implementation is largely determined by stable access to water, coordination of farmer institutions, intensive extension support, and the availability of capital and supporting infrastructure. Production risks due to climate change and pest attacks also have a significant impact on yield stability, requiring integrated mitigation strategies such as simultaneous planting and strengthening of integrated pest management (IPM). Overall, this study confirms that rice production enhancement strategies must be integrative, adaptive, and sustainable by strengthening the synergy between technology, institutions, and supporting policies. These findings are expected to serve as a basis for formulating more effective agricultural policies to boost national rice production.